O museu no estudo da geografia dos anos iniciais do ensino fundamental - Cucchi, Andréia Zuchelli (2022)
This thesis entitled: “The Museum in the Study of Geography in the Early Years of Elementary School” is the result of research linked to the Research Group: Representations, Spaces, Times and Languages in Educational Experiences – RETLEE, of the Postgraduate Program in Geography – Doctorate – Concentration area: Production of Space and Environment, Research line: Education and Teaching of Geography, from the State University of Western Paraná – UNIOESTE/ Francisco Beltrão Campus. The objective is to evaluate the sense and pedagogical significance of the museum for the teaching and learning of Geography, in the time-space relationship, in the Early Years of Elementary School. The development arose from an alternative didactic-pedagogical proposal to the study of Geography, which was carried out with students from the 3rd years of the Early Years of Elementary School at Professor Pedro Algeri Municipal School of Francisco Beltrão/PR, with the purpose of building, organizing and socializing an exhibition in the form of a museum in the school environment itself to study the geographic contents planned for the participating school stage. The contents developed in the museological activity contemplated the provisions of the Curricular Pedagogical Proposal of the school. In the construction and organization of the museum, there was the direct participation of the regent teachers of classes, students and family members, in the field research, collecting photos, images and objects, which were used in the exhibition and in the making of collective materials. The materials were shown in the exhibition of the school museum, with the purpose of studying the place and the transformations that have taken place in space, from the time-space analysis. In addition to the use of materials brought by students and families in discussions and exposition, there was also the construction of representative texts and drawings with the synthesis of learning, making banners and panels and the visit to the Colonization Museum, activities that made it possible to energize the way content was presented in Geography classes. In addition to the study of the place, contents related to the study of the local and its relationship with the global were also developed, study on the proximities and differences between the countryside and the city and the study of the impacts of human action on nature. As activities provided in the exhibition, students can reflect on the meaning and significance of geographic content for the educational process and for citizens. The evaluation carried out with teachers, students and family members showed that the construction, organization and socialization of the exhibition in the form of a school museum for the study of Geography was presented as a viable didactic-pedagogical alternative to the teaching and learning process of geographic knowledge. The activities produced significant results in the field of geographic education, because there was the engagement of all the parts in the materialization of the whole and in the process of construction of the geographic knowledge; the result of these actions was shared through the school museum with participants, students, teachers, family members and the school community. Result that we intend to share with the Municipal Department of Education of Francisco Beltrão/PR, in view of the possibilities of carrying out with the Initial Years of Elementary School for the study of Geography.